ACI/EG eutectic mixture mediated synthesis, characterization and in vitro osteoblast differentiation assessment of spiropyrrolo[1, 2-b]isoquinoline analogues. Issue 29 (2nd May 2018) - Periyasami, Govindasami; Arumugam, Natarajan; Rahaman, Mostafizur; Kumar, Raju Suresh; Manikandan, Muthurangan; Alfayez, Musaad A.; Premnath, Dhanaraj; Aldalbahi, Ali
Abstract : An eco-friendly acetylcholine iodide–ethylene glycol (ACI/EG) deep eutectic mixture mediated green protocol has been developed for the synthesis of unexplored multi-functionalized linear tricyclic spiropyrrolo[1, 2- b ]isoquinoline analogues. Abstract : An eco-friendly acetylcholine iodide–ethylene glycol (ACI/EG) deep eutectic mixture mediated green protocol has been developed for the synthesis of hitherto unexplored multi-functionalized linear tricyclic spiropyrrolo[1, 2- b ]isoquinoline analogues. The effects of the synthesized compounds on the osteoblast differentiation of hBMSC-TERT cell lines were investigated and promising results were observed with significant IC50 values. In addition, molecular modeling simulations were also performed with the 3D structure of BMP-2 to reveal binding interactions and orientations of highly potent spiropyrrolo[1, 2- b ]isoquinoline analogues.